2020
DOI: 10.1002/celc.202000523
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Alkaline Stability of Composite Anion Conducting Ionomers Based on Poly(phenylene oxide) Grafted with DABCO and Mg/Al Lamellar Double Hydroxide

Abstract: We studied composite anion exchange membranes made from poly(2,6-dimethyl-1,4phenylene oxide) (PPO) with grafted 1,4-diazabicyclo[2.2.2]octane (DABCO) and Mg/Al lamellar double hydroxide particles as inorganic filler. The mechanical and conductivity properties were measured in fully humidified conditions. The activation energy for conductivity amounts to (0.20 ± 0.01) eV. The degradation of the anion exchange membrane in 2 M NaOH at 60 °C was investigated during 168 h following the ionic conductivity, water up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Composite membranes with DABCO-PPO and 30 wt% MgAl-LDH were prepared in 2020 by Pasquini et al [49]. The high amount of the second phase was chosen in order to understand the effect of the inorganic filler on alkaline and hydrolytic degradation.…”
Section: Poly(phenylene Oxide) (Ppo)mentioning
confidence: 99%
“…Composite membranes with DABCO-PPO and 30 wt% MgAl-LDH were prepared in 2020 by Pasquini et al [49]. The high amount of the second phase was chosen in order to understand the effect of the inorganic filler on alkaline and hydrolytic degradation.…”
Section: Poly(phenylene Oxide) (Ppo)mentioning
confidence: 99%
“…Over the last decade, several polyarylene ether (PAE) polymers have been widely adopted as the backbone in AEMs because of their good mechanical properties, film-forming ability, and thermal stability. Many innovative AEMs have been developed based on polymer backbones such as polyether ether ketone, [73,74] polyphenylene oxide (PPO), [75,76] polybenzimidazole, [77,78] and polyethersulfone [79,80] (Figure 4a). Recent reports have revealed that not only cations but also polymer backbones can undergo nucleophilic attack by OH À , resulting in polymer degradation, especially when polar bonds such as ether and sulfone are present in the backbones.…”
Section: Strategies For Polymer Backbonesmentioning
confidence: 99%
“…Various strategies have been explored to decrease the degradation [18] including a change of the polymer backbone [19,20], the introduction of long side chains, [21][22][23][24], and the delocalization of the positive charge [13,25]. Similarly, the use of composites with stable inorganic materials in alkaline environments such as hydrotalcites have shown an improvement in mechanical properties [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%